Manajemen Sumber Daya Manusia - Sakban Sakban; Ifnaldi Nurmal; Rifanto Bin Ridwan (Journal Of Administration and Educational Management (ALIGNMENT), 2019)
The purpose of this study was to determine human resource management in the Madrasah Aliyah Al-Mathitiriyah Rupit District. This type of research is qualitative research with descriptive analytical methods, namely methods that attempt to systematically explain the discussion material originating from various sources for later analysis in order to obtain results as a conclusion. Research Results, principals are very instrumental in increasing and motivating teachers, staff / employees, in improving student achievement, which has been effective and conditional. In providing opportunities and opportunities for the teachers to take part in education and training held by the government and provide opportunities for teachers to continue their higher level of study, Conclusion, the head of MA Al-Mathiriyah carries out, plans, and professionals, as well as field experts, and able to give awards, and provide penalties, if it violates the teacher's code of ethics. Keywords: Human Resource Management, Performance